Isolation and identification of major cockroaches associated pathogenic bacteria in Bonga town, Ethiopia - Gebreegziabher Gebreyohans; Nafyad Ibrahim Batu; Tegegn Muche; Nigus Kalayou; Ketema Bacha; Soressa Gershe; Zerihun Ango (The Microbe)
Cockroaches are a reservoir of various pathogenic microorganisms that pose a significant risk to public health because of unsanitary living spaces, poor waste management, inappropriate food storage, limitations of public health guidelines, and education on hygiene practices. The aim of this study was to isolate and identify major pathogenic bacteria associated with cockroaches in Bonga Town, Kaffa Zone. A total of 300 cockroaches were collected from Restaurants, Houses, and Hospitals, with 100 specimens from each location. The collected cockroaches were then subjected to microbiological analysis in the laboratory to identify potential bacterial pathogens. The cockroaches were killed using cotton-soaked chloroform, surface-sterilized using 70 % ethanol, and dissected aseptically. The cockroaches were added to 2 mL of sterile normal saline and shaken thoroughly for two minutes. The cockroaches were taken out of the tubes, and the remaining liquid was centrifuged at 2000 rpm for 10 minutes. The supernatants were then removed, and the remaining sediments were used for culture. In each tube, a fixed volume of 1 mL of the sediments was cultured on various culture media separately. Different species of bacteria with similar morphological characteristics were identified on the external and internal surfaces of the cockroaches. These results indicate the morphological characteristics of the colonies grown on each agar plate in different settings (Hospital, Restaurants and Households). The specific characteristics of the colonies can help in identifying different bacterial species. The isolated pathogens were then identified using standard microbiological techniques, including gram staining, morphology, microscopic slides, and biochemical tests. The results revealed the presence of bacterial pathogens, including E. coli, Salmonella, Pseudomonas, Staphylococcus spp., Shigella spp., and Proteus spp. The bacterial species were predominantly found in Households and Hospital areas, while fewer were found in restaurant areas. The presence of these pathogenic bacteria in cockroaches highlights the potential risk of food contamination and subsequent human diseases. Therefore, further analysis and characterization of these pathogenic bacteria should be done at the molecular level, and more clinical evaluation must be undertaken after the final identification and characterization.